2011
DOI: 10.1097/fbp.0b013e32834aff98
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin, a 5-HT2A inverse agonist, reverses psychosis-like behaviors in a rodent model of Parkinson's disease

Abstract: Parkinson's disease psychosis (PDP) is a condition for which a safe, tolerated, and effective therapy is lacking. Treatment with typical or atypical antipsychotics may be contraindicated in patients with PDP because of the potential for aggravating motor symptoms. This study used a novel animal model with features of both Parkinson's disease (PD) and psychosis to examine a potential mechanism for reversing PDP. Animals with bilateral 6-hydroxydopamine lesions of the substantia nigra displayed motoric impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…Use of the selective 5-HT2A antagonist pimavanserin has been shown to resolve psychotic behavior in an animal model (6-hydroxydopamine), while in clinical trials use of pimavanserin, previously demonstrated to be well tolerated, has more recently been reported to have a beneficial effect on VH in PD patients [56][57][58].…”
Section: B)c) Serotoninmentioning
confidence: 99%
“…Use of the selective 5-HT2A antagonist pimavanserin has been shown to resolve psychotic behavior in an animal model (6-hydroxydopamine), while in clinical trials use of pimavanserin, previously demonstrated to be well tolerated, has more recently been reported to have a beneficial effect on VH in PD patients [56][57][58].…”
Section: B)c) Serotoninmentioning
confidence: 99%
“…Other receptor drug targets for which ligands have been developed include the serotonin 5-HT 2A receptor (highly selective 5-HT 2A receptor inverse agonists have been hypothesized to provide symptomatic control in patients suffering from PD psychosis) [122] (pimavanserin) [123] and the a-2 adrenergic receptor [124] (fipamezole: a-2 adrenergic receptor antagonists such as fipamezole have been shown to alleviate Ldopa-induced dyskinesia and enhance the duration of the antiparkinsonian action of L-dopa) [125].…”
Section: Gene Therapymentioning
confidence: 99%
“…Compensatory excessive dopaminergic signaling in response to striatal degeneration was impacted by pimavanserin. However, the normal dopaminergic response to amphetamine in nonlesioned animals was not impaired [McFarland et al 2011].…”
Section: Mechanism Of Action Of Pimavanserinmentioning
confidence: 99%
“…The compound was readily bioavailable at 10 mg/kg orally [Vanover et al 2006]. It has also been studied in rodent models of PDP [McFarland et al 2011;Vanover et al 2008]. Pimavanserin reduced psychotic behaviors (increased or altered head twitches) after treating rats with fenfluramine, a serotonin releasing agent [McFarland et al 2011].…”
Section: Mechanism Of Action Of Pimavanserinmentioning
confidence: 99%
See 1 more Smart Citation